Prescribing Trends for Valproate Among Pregnant Women: A Cross-sectional Study in 2013 and 2016 Using the French Health Insurance Database. (24th May 2022) - Degremont, Adeline; Kerbrat, Sandrine; Balusson, Frédéric; Jonville-Bera, Annie Pierre; Ringa, Virginie; Travers, David; Tillaut, Hélène; Leray, Emmanuelle; Oger, Emmanuel; Biraben, Arnaud; Polard, Elisabeth
Abstract : Background and Objective: To describe the prescribing trends for sodium valproate (VPA) and alternative drugs during and around pregnancy, comparing 2016 (after the recommendations on valproate for women were reinforced by the European Medicines Agency [EMA]) with 2013 (before the recommendations). Methods: Using the French National Health Insurance Database, a cross-sectional study was carried out in 2013 and in 2016, including women who became pregnant and had at least 1 reimbursement claim for VPA in the 2 years prior to pregnancy or during pregnancy. Exposure to VPA and its alternatives was then measured for each quarter, in the 2 years before pregnancy (preconception), during pregnancy, and in the year after pregnancy (postpartum). Results: Among pregnant women with epilepsy (n = 2, 607 pregnancies), the proportion exposed to VPA during pregnancy decreased from 26.4% to 9.3% between 2013 and 2016, alongside an increase in lamotrigine and levetiracetam use. Among pregnant women with bipolar disorder (n = 4, 278 pregnancies), the proportion of women exposed during pregnancy decreased from 3.7% in 2013 to 1.9% in 2016, without any switch to alternative drugs. In both populations, fewer than one third had consulted a specialist before pregnancy. Discussion: As recommended by the EMA, a change in practice over the 2013–2016 period was observed, with fewer women exposed to VPA during pregnancy and before pregnancy. However, in 2016, a large number of women were exposed to VPA in the first trimester of pregnancy (n = 471), which could suggest that the timing of pregnancy should be better planned when possible.